2017
DOI: 10.1002/acm2.12148
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of array detector measurements in determining shifts of MLC leaf positions

Abstract: Using a MatriXX 2D ionization chamber array, we evaluated the detection sensitivity of systematically introduced MLC leaf positioning shifts to test whether the conventional IMRT QA method can be used for quality assurance of an MLC tracking algorithm. Because of finite special resolution, we first tested whether the detection sensitivity was dependent of the locations of leaf shifts and positions of ionization chambers. We then introduced the same systematic leaf shifts in two clinical intensity modulated rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…To achieve better than 1 mm accuracy and precision of MLC leaf positioning, routine MLC QA testing is recommended by TG-142 [11] to be performed weekly using visual inspection of matched segments and monthly quantitative testing using a special test pattern such as a picket fence test described by Losasso [3]. Different methods have been described in the literature for MLC QA to deliver IMRT/VMAT plans accurately [18,[23][24][25][26]. One of the used methods for MLCQA for IMRT/VMAT delivery was the twodimensional (2D) evaluation of either film or scanned image by visual inspection, which are subjective, timeconsuming, sensitive to external conditions, and a less accurate way to define MLC positioning errors [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve better than 1 mm accuracy and precision of MLC leaf positioning, routine MLC QA testing is recommended by TG-142 [11] to be performed weekly using visual inspection of matched segments and monthly quantitative testing using a special test pattern such as a picket fence test described by Losasso [3]. Different methods have been described in the literature for MLC QA to deliver IMRT/VMAT plans accurately [18,[23][24][25][26]. One of the used methods for MLCQA for IMRT/VMAT delivery was the twodimensional (2D) evaluation of either film or scanned image by visual inspection, which are subjective, timeconsuming, sensitive to external conditions, and a less accurate way to define MLC positioning errors [25].…”
Section: Discussionmentioning
confidence: 99%
“…Different methods have been described in the literature for MLC QA to deliver IMRT/VMAT plans accurately [18,[23][24][25][26]. One of the used methods for MLCQA for IMRT/VMAT delivery was the twodimensional (2D) evaluation of either film or scanned image by visual inspection, which are subjective, timeconsuming, sensitive to external conditions, and a less accurate way to define MLC positioning errors [25]. Another method that does not require physical measurements for MLCQA, gantry angle, collimator angle, and stored cumulative dose per control point would be retrospectively analyzed via the MLC log files recorded by the machine end of each IMRT/VMAT delivery.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the device is capable of detecting leaf bank errors at this field size. Shang, Godley, Huang, Qi, and Xia (2017) assessed the sensitivity of the MatriXX detector to ±1 and 2 mm alterations of MLC leaves of two IMRT plans of prostate and head-and-neck cancers. Their study reported that the MatriXX is sensitive to leaf positioning shifts of ±2 mm with a pass rate of 95% at gamma criterion of 3%/3 mm.…”
Section: Octaviusmentioning
confidence: 99%
“…This was followed by the I'MRT MatriXX (2D array) using a 3%/3 mm gamma criteria, then the single ion chamber measurement. Shang et al shifted the MLC leaves on one side of the bank by 1-4 mm and found that the MatriXX was able to detect a 2 mm shift with a 3%/3 mm gamma criteria and a 1 mm shift with a 2%/2 mm criteria [35].…”
Section: Introductionmentioning
confidence: 99%